Varicocelectomy For Infertile Men with Clinical Varicocele and Normal Semen Parameters, In Relation to Pregnancy Rate and Recurrent Spontaneous Miscarriage Incidence: A Systematic Review - I Komang Bintang Satria Mahaputra; I Made Udiyana Indradiputra; I Dewa Gede Reza Sanjaya (Brawijaya Journal of Urology, 2023)
Objectives. Current guidelines suggest performing varicocelectomy only for men with clinical varicocele, infertile, abnormal semen parameters, and impaired testicular development. Varicocelectomy in infertile men with normal semen parameters was deemed to not benefit fertility significantly. The purpose of this systematic review is to discuss articles that studied varicocelectomy in men with clinical varicocele, normal semen analysis, and normal women who experience infertility or spontaneous miscarriage and find out whether there is an improvement in pregnancy and live birth rate.Methods. The databases used for searching articles in this study are PubMed and Cochrane using the keywords “varicocele”, “normal semen parameters”, “recurrent miscarriage”, “sperm DNA fragmentation”, and “infertility”. The outcome of the articles sought is pregnancy rates and miscarriage rates after varicocelectomy.Result. After carrying out the article selection process, there are 2 articles used. One study is a randomized control trial and another one is a non-randomized control trial. All enrolled patients had varicocele and normal semen analysis results according to WHO guidelines 2022. The average pregnancy rate after varicocelectomy at a 12-month follow-up interval was 51% in the varicocelectomy group vs 25% in the control group. The average miscarriage rate was 6% in the varicocelectomy group vs 34% in the control group. One study showed a correlation between decreasing Sperm DNA fragmentation and pregnancy rate.Conclusion. Varicocelectomy may provide benefits in infertile couples and cases of recurrent spontaneous miscarriage with normal female factors and men with varicocele with normal semen parameters.